Should Capital Flows Be Regulated? A Look at the Issues and Policies - Islam, Roumeen (World Bank, Washington, DC, 2014)
The author argues that externalities in financial markets, implicit and explicit guarantees on financial transactions, and information asymmetries in financial markets that may exacerbate contagion provide a rationale for a government role in managing the risk associated with cross-border capital flows. Governments can complement private sector risk management with measures that help deal with the volatility of capital flows. These measures include those that control the type and volume of capital flows and those that help investors make better investment decisions, and that may reduce herding behavior, such as better information provision. The main instruments that have been tried or recommended since the onset of the recent financial crises can be grouped in several categories. 1) Debt management: The composition, maturity structure, and level of external debt have played an important role in financial crises. High short-term debt relative to liquid assets has been found to be consistently correlated with financial crises in recent times. Governments can affect the level of debt (including private debt) and its composition, though the mix of policies they use will vary. Prudential regulation in the financial sector, corporate sector regulation, and restrictions on capital movements have all been used with varying success to change the level and composition of external debt. 2) Other macroeconomic policies: Most countries that have suffered macroeconomic crises have had fixed exchange rate systems; some have not. But whether or not a country has a fixed exchange rate is not the relevant question. The question is instead whether there is reason to expect a significant weakening of the currency, possibly as a result of a change in policy stance. Large real exchange rate appreciations have been among the main reasons for runs on currency; macroeconomic policy needs to be aimed at managing these. With a fixed exchange rate regime, flexibility must be maintained elsewhere in the economy. Policymakers may need to make tradeoffs between price and output stability once market jitters have set in. There is no single right answer to the question of which to emphasize more at a given time; it depends on a country's circumstances. 3) Risk management in the financial sector: The health of the financial sector is related to the government's fiscal position, its macroeconomic policies, and financial crises. The regulatory and supervisory frameworks in developing countries need to be adapted to the special features of these markets. Many developing countries are subject to frequent trade and capital account shocks, while lacking the means to deal with these shocks, such as adequate insurance markets. This situation may call for policies that nor only affect the incentives of lenders, but also help manage risk more directly. Examples of such policies include maturity, and liquidity requirements. 4) Information and transparency: More disclosure of information and improvements in the quality of that information could reduce the volatility that arises from herding behavior. Ex ante, they may also have a beneficial effect on the allocation of capital.